FAILURE TO INFORM THE ACCUSED OF THE RIGHT TO REMAIN SILENT CONSTITUTES RELATIVE NULLITY CONTINGENT ON PROOF OF PREJUDICE (CIPEEX, 2025)
This paper analyzes the omission to advise defendants of their right to remain silent— a safeguard under Brazil’s Federal Constitution (art. 5, LXIII) and the American Convention on Human Rights (art. 8)—and its impact on the validity of procedural acts. It is a doctrinal and case-law review addressing constitutional and conventional grounds against self-incrimination, the principle of procedural instrumentalism, and Superior Court of Justice precedents, including Habeas Corpus 207,786/PR. The aim is to set practical criteria for recognizing (or rejecting) nullity where the defendant was not informed of the right to silence. Methodologically, the analysis considers whether, if duly warned, the defendant would have remained silent and whether that choice could have affected the defense. The findings indicate that nullity is relative: omission does not automatically invalidate the act and requires proof of concrete prejudice; mere formal error does not suffice. The conclusion is that requiring demonstrated prejudice reconciles protection against self-incrimination with procedural efficiency and distinguishes the scenario from absolute nullities, which do not require harm.